Combined magnetic resonance imaging and high resolution spectroscopy approaches to study the fertilization effects on metabolome, morphology and yeast community of wine grape berries, cultivar Nero di Troia. (15th February 2019) - Ciampa, Alessandra; Dell'Abate, Maria Teresa; Florio, Alessandro; Tarricone, Luigi; Di Gennaro, Domenico; Picone, Gianfranco; Trimigno, Alessia; Capozzi, Francesco; Benedetti, Anna
Highlights: Mineral (M) or organo-mineral (OM) fertilization affected Nero di Troia grape berries qualities. High field resonance magnetic techniques detected differences in M and OM wine grape berries. MRI revealed lower mean diameter and higher T1 relaxation time in OM grape berries. 1 H NMR metabolic profiling of M and OM grape berries differed in some primary metabolites. Also presence and distribution of some yeasts isolated from grape berries in M and OM vines differed. Abstract: Effects of fertilization practices, mineral (M) and organo-mineral (OM), on molecular composition of Nero di Troia cultivar grape berries was studied using conventional chemical analysis, Magnetic Resonance Imaging (MRI) and 1 H NMR spectroscopy on intact berries and extracts, respectively, and through analysis of yeast species developed on grape skins. Plants vegetative status did not differ between the two fertilization practices, whereas some grape juice chemical characteristics differed in fertilized grapes. MRI provided information on grape berries morphology through weighted images depending on spin-spin (T2) and spin-lattice (T1) relaxation times. T1 values were the highest in OM grape berries. 1 H NMR metabolic profile, combined with chemometric analysis, evidenced significant differences for some metabolites (valine, leucine, isoleucine, proline, and malic acid). Furthermore, higher frequency of yeasts genus Starmella sp., isolated from OM grape berries contributed to reinforcing the found results on the physiological response of wine grape Nero di Troia to fertilization.